SISTEM PRESIDENSIAL DAN PENGELOLAAN KOALISI, BERDASARKAN TIGA TAHUN PEMERINTAHAN PRESIDEN JOKO WIDODO [PRESIDENTIAL SYSTEMS AND MANAGEMENT OF COALITIONS, BASED ON THREE YEARS OF GOVERNMENT PRESIDENT JOKO WIDODO] - Nfn Efriza (Jurnal Politica, 2018)
This paper discusses the relationship between the President and the House of Representatives and the coalition government based on the three years of President Joko Widodo (Jokowi), who was trapped in inter-institutional competition as a consequence of a mixture of presidential and multi-party systems. In outlining the problems we use the rationale of Scott Mainwaring and David Altman on the combination of presidential and multiparty systems as well as coalitions in presidential systems. Completed analysis of Otto Kirchheimer on Catch All Party, to outline the transformation of the party in this modern era. Accompanied by a discussion on the orientation of political parties in Indonesia, based on Yasraf Amir Piliang's description of political nomadism. Based on the above facts and thoughts, produced by presidential and multiparty system and the way of government conducted by President Jokowi, is the management of “fat” coalition with accommodative leadership and transactional philosophy. The nature of the management is an attempt to maintain a harmonious relationship between the President and the House of Representatives with the consequence that President Jokowi violates his commitment to realize an unconditional coalition and not share for power seats.Tulisan ini membahas relasi Presiden dengan Dewan Perwakilan Rakyat (DPR) dan pengelolaan koalisi berdasarkan tiga tahun kepemimpinan Presiden Joko Widodo (Jokowi), yang sempat terjebak dalam ketegangan antarlembaga sebagai konsekuensi dari perpaduan antara sistem presidensial dan multipartai. Dalam menguraikan permasalahan digunakan dasar pemikiran dari Scott Mainwaring dan David Altman mengenai kombinasi sistem presidensial dan multipartai serta koalisi dalam sistem presidensial. Dilengkapi analisis dari Otto Kirchheimer tentang Catch All Party, untuk menguraikan tranformasi kepartaian di era modern ini. Disertai pembahasan mengenai orientasi partai-partai politik di Indonesia, berdasarkan uraian Yasraf Amir Piliang tentang nomadisme politik. Berdasarkan realitas dan pemikiran di atas, dihasilkan bahwa kombinasi sistem presidensial dan multipartai dan cara pengelolaan pemerintahan yang dilakukan oleh Presiden Jokowi, adalah pengelolaan koalisi bersifat “gemuk” dengan kepemimpinan yang akomodatif dan cenderung transaksional. Sifat pengelolaan tersebut sebuah upaya menjaga hubungan harmonis antara Presiden dan DPR  dengan konsekuensi bahwa Presiden Jokowi melanggar komitmennya untuk mewujudkan koalisi tanpa syarat dan tidak bagi-bagi kursi kekuasaan.